Crusted scabies in a chid with systemic lupus erythematosus - Wanke,Nurimar C.F. (1992)
A child with systemic lupus erythematosus who has been treated with prednisone for three years, developed crusted scabies. Scrapings from lesions revealed Sarcoptes scabiei adult mites mad eggs. The patient died with septicemia and renal failure soon after starting topical 20% sulfur. A marked improvement was observed in the cutaneous lesions.